The Influence of Government Accounting Standards and Internal Control Systems on the Quality of Regional Financial Reports with Accountability as a Moderating Variable - M Firza Alpi (CERED Indonesia Institute, 2025)
This study aims to analyze and determine the effect of government accounting standards and internal control systems on the quality of regional financial reports, with accountability as a moderating variable (an empirical study in Medan City Regional Apparatus Organizations). Therefore, this research analysis can educate readers about the quality of Medan City regional financial reports. This study uses a quantitative approach with a questionnaire as the data collection technique with 78 samples. The analysis method used is the Statistical Program for Social Science (SPSS). The results of this study indicate that government accounting standards and internal control systems influence the quality of regional financial reports